Concept and Practice of Receiving and Disseminating News in Islam - Rahman Rifa'i; Fadhilah Fadhilah; Nazhiful Fajri; Selvita Yernis (UKAZ: International Journal of Islamic Studies, 2025)
Receiving and disseminating news is one of the aspects regulated by Islam related to human relations. News has an important role in society so that the process of receiving and disseminating it needs to be done carefully to avoid misunderstandings in the community. This study aims to understand the concept and practice of receiving and disseminating news in Islam. This research uses a qualitative method with the type of living Quran and Hadith research whose data sources are taken from the Quran, Hadith, scholars' ijtihad and experts' opinions. In addition, the author also strengthens the research results by using various previous research results. All the data above were analyzed thematically using Milles and Hubberman's interactive analysis technique. The findings of this study found four concepts and practices of receiving and disseminating news in Islam. The four concepts and practices of receiving and spreading news in Islam are i) tabayyun, ii) following what is understood, iii) tajannub al-huzn, iv) not spreading false news and disgrace. The four concepts and practices of receiving and disseminating news in Islam can serve as guidelines for individuals and media organizations to be careful in receiving and disseminating news.